(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to build a strategy according to students of the Institute of Fine Arts in the subject of pictorial composition, and then measure the size of the effect of the strategy of visual intelligence to develop the skills of pictorial composition. For the students of the Institute of Fine Arts in the subject of pictorial composition, the researcher built and synthesized a strategy according to visual intelligence, consisting of (visual thinking networks, visual imagination strategy, for scientific and cognitive learning, according to organized steps that were followed and became the following form (presenting the idea, presenting the concept, dividing students into groups, mental imagination, drawing the imagined idea, discussing students in their drawings, organizing ideas, final formulation of the concept, evaluation). The third stage - Department of Fine Arts (drawing) - Institute of Fine Arts Diyala - for boys and girls. Their number reached (28) students who were randomly distributed, with (14) students in the experimental group studied using the strategy of visual intelligence, and (14) students in the The control group was studied in the The researcher prepared two tools for the current research: 1-The cognitive test to measure the skills of students (the research sample), which consisted of (50) items 2-The skill test tool (observation form). The observation form consisted of (20) items The researcher used the following statistical methods to process And data processing, the researcher used (Wilcoxon) test for correlated samples and (Mann-Whitney) test for average samples, item difficulty coefficient, item discrimination coefficient. . ., Among the most important results of the current research :: 1-The study plans prepared in the current research according to the strategy of visual intelligence led to the development of the skills of the students in the same research in pictorial composition and to their mastery of it at a rate that exceeds the degree of criterion, and the percentage reached (85%). 2-These results confirm the impact of the study plans prepared in the current research according to the strategy of visual intelligence in developing the skills of the students of the third stage - the Department of Fine Arts at the Institute of Fine Arts in relation to the subject of graphic composition.. Conclusions: 1-The strategy of visual intelligence contributed to the development of the performance of artistic skills from the pictorial composition subject of the students of the Institute of Fine Arts. 2-It helps students to learn by watching, and gives them an opportunity to learn through a beautiful experience. 3-Making the most of the visual intelligence strategy in the cognitive and skillful achievement of students in the composition subject. Recommendations: 1-Directing the institutes of fine arts, colleges, and technical departments concerned with teaching pictorial composition to try to move away from traditional methods and rely on the teaching method prepared in the current research and benefit from the results of the research Composition:. 2-Working on preparing the specialized studio and providing all the capabilities and requirements to implement the study plans prepared in the current research Suggestions: The researcher suggested conducting the following studies: 1-The impact of the visual intelligence strategy on developing students’ skills in other subjects such as(planning, colors, perspective, murals, sculpture, theater( 2-Conducting a study similar to the current study to develop skills in practical courses for teachers of art education